All-Optical Actively Mode-Locked Fiber Laser at 2-μm Based on Interband Modulation - Xu Wu; Zhichao Wu; Tianye Huang; Bingwei Chen; Kaixuan Ren; Songnian Fu (IEEE Photonics Journal)
In this paper, we have achieved a high repetition rate and tunable pulse generation near ∼2 μm through an all-optical actively mode-locked fiber laser. The performances of the fiber laser have been systematically investigated through numerical simulations. The thulium-doped fiber laser cavity is modulated by the optical injection at 1.55 μm via a nonlinear optical loop mirror in which a specially-designed group-velocity-matching highly nonlinear fiber is incorporated. According to the simulation results, up to 40-GHz pulse train with picosecond tunable pulse width and peak power can be produced. Moreover, the repetition rate can be further enlarged with the help of higher gain. The impacts of gain coefficient, cavity length, and repetition rate on the output are studied in details. The proposed mode-locked fiber laser can be potentially used for future 2- μm fiber communication.